2017
DOI: 10.1088/1873-7005/aa7406
|View full text |Cite
|
Sign up to set email alerts
|

Further analysis of the budgets of the dissipation tensor ${\varepsilon }_{{ij}}$ in turbulent plane channel flow

Abstract: Abstract. Recent DNS results [Gerolymos G.A., Vallet I. : J. Fluid Mech. 807 (2016) have provided data for the terms in the transport equations for the components of the dissipation tensor ε ij in low-Reynolds turbulent plane channel flow. The present paper extends the previous results by a detailed analysis of the behaviour of various mechanisms in the ε ij -transport equations (production, diffusion, redistribution, destruction), with particular emphasis on the component-by-component comparison with the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The data are in excellent agreement (Gerolymos and Vallet 2016, figures 8-9) with those of Vreman and Kuerten (2014a) who studied the variances of the components of the velocity gradient (Vreman and Kuerten 2014b). Details on the numerical method (Gerolymos et al 2010) and on the computation of statistics were reported in previous work (Gerolymos and Vallet 2017).…”
Section: Tpc Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…The data are in excellent agreement (Gerolymos and Vallet 2016, figures 8-9) with those of Vreman and Kuerten (2014a) who studied the variances of the components of the velocity gradient (Vreman and Kuerten 2014b). Details on the numerical method (Gerolymos et al 2010) and on the computation of statistics were reported in previous work (Gerolymos and Vallet 2017).…”
Section: Tpc Flowmentioning
confidence: 99%
“…represent the componentality of the small scales. Previous explorations of the componentality of various tensors in wall turbulence (Mansour et al 1988, Jovanović 2004, Gerolymos and Vallet 2016) have been particularly useful, not only regarding wall-asymptotic behaviour (Gerolymos and Vallet 2017), but also in clearly delimiting via AIM a strictly inner region (Krogstad and Torbergsen 2000) where outer scaling does not apply, i.e. the outer limit of the buffer zone ( ⪅ + y 80).…”
Section: Introductionmentioning
confidence: 99%